Konjunktureller Beitrag des Baugewerbes – in der Corona-Krise und darüber hinaus. - Bauer, Stefanie; Lehr, Ulrike; Thobe, Ines; Ulrich, Philip; Wolter, Marc Ingo (My University, 2021)
Welche Handlungsmöglichkeiten ergeben sich für politische Entscheidungsträger*innen, den ökonomischen Folgen konjunktureller Einbrüche wie z. B. der Coronavirus-Krise entgegenzuwirken? Ein mögliches Handlungsfeld ist die energetische Gebäudesanierung. Inwiefern diese geeignet ist, kurzfristig einen Beitrag zur konjunkturellen Stabilisierung zuleisten, diesre Frage wird in dem Bericht nachgegangen. Darüber hinaus werden mögliche politische Maßnahmen zur Vermeidung von Emissionen des Gebäudebestandes diskutiert, die das Baugewerbe hinsichtlich seiner Kapazitäten herausfordern, aber auch eine längerfristige Perspektive aufzeigen.

What options are there for political decision-makers to counteract the economic consequences of economic downturns such as the coronavirus crisis? One possible field of action is the energy-efficient refurbishment of buildings. This report examines the extent to which this is suitable for contributing to economic stabilization in the short term. In addition, possible political measures to prevent emissions from the building stock are discussed, which challenge the construction industry in terms of its capacities, but also show a longer-term perspective.Even if the initial situation of the construction industry in February 2020 was still accompanied by capacity limitations, the coronavirus crisis also burdened this industry. In this context, the opportunity arose not only to support the economy with measures for energy-efficient refurbishment, but also to do something for climate protection. Energy-efficient refurbishment of buildings holds considerable potential in the transition from crisis mode to post-crisis mode against the background of the new normal. It strengthens the construction industry, creates local employment, absorbs released skilled workers and reduces energy demand and emissions in the long term. However, the task of refurbishing buildings to make them more energy-efficient is a long-term undertaking - a marathon run, so to speak. In order to implement this, concrete measures for the medium-term perspective should be prepared and initiated now. Implementation can only succeed if there is a sufficient workforce. To this end, working conditions in the construction industry should be improved. After all, a monitoring process is also required for target achievement, which records successes and difficulties as promptly as possible so that timely intervention can be taken if the target path is abandoned. Working conditions or measures can then be readjusted.
Keywords: Energetische Gebäudesanierung; Bauwirtschaft; Krisensituation; Konjunkturentwicklung; Konjunkturpolitik; Beschäftigter; Arbeitsbedingung; Corona-Krise